STUDI ETNOBOTANI TUMBUHAN BERKHASIAT OBAT PADA SUKU TAU TAA WANA DI DESA BULAN JAYA KECAMATAN AMPANA TETE, KABUPATEN TOJO UNA UNA, PROVINSI SULAWESI TENGAH - Hijrah Hijrah; Arsa Wahyu Nugrahani; Ramadanil Ramadanil (Biocelebes, 2019)
Ethnobotanical study of Tau Taa Wana Tribe aims to determine the types and parts of plants used as traditional medicine as well as knowing how to use medicinal plants by Tau Taa Wana Tribe in the Bulan Jaya Village Ampana Tete District, Tojo Una Una Regency, Central Sulawesi Province. The study was a descriptive research using qualitative methods with the technique of sampling snowball sampling. Information obtained through open-ended interviews at 9 informants interviewed based on the questions that had been developed previously. The results showed that there were 69 species of plants that are divided into 38 families used as medicine. The most widely used plants originate from Asteraceae and Solanaceae family each 5 species. Part used include leaves, stems, fruits, roots, rhizomes, tubers, herbs, seeds, bark and flowers. Percentage of part medicinal plants most widely used are the leaves (32%). The most used method is to be drunk.